Fine Art Theory, Its Type and Genre - Rakhmonkulov Khamrokul Bobokulovich (Genius Journals, 2022)
This article is about the theory of fine art and its type genre, general concepts, parts and sections, information is covered in an overview
Keywords: Social life; purpose of illustration; content; work